Pengaruh Tingkat Pengetahuan Dan Persepsi Diri Terhadap Keputusan Membeli Makanan Bergizi Bagi Mahasiswa - Roisu Eny Mudawaroch (Universitas Muhammadiyah Purworejo, 2019)
This study aims to determine how much the relationship of knowledge about nutrition to the decision to buy nutritious food and self-perception of the decision to buy nutritious food. The method in this research is descriptive quantitative research method. Respondents in this study were students of the Faculty of Agriculture, University of Muhammadiyah Purworejo levels I and II, totaling 90 respondents. The data collection of this study used a questionnaire method. The scale used in this study is a Likert scale. The test is a description, multiple linear, and F test. The results of this study indicate that the majority of samples were female, amounting to 52.2% with the largest number aged 19 years at 41.1%. Most respondents live with their parents, which is 64.4%. Most respondents get a monthly allowance of 255-500 thousand rupiahs, which is 42.2 percent. Costs incurred to buy monthly food amounted to 255-500 thousand rupiahs, amounting to 47.8 percent. A validity test conducted on three variables shows all data is valid. Linear regression test showed a positive relationship with the regression equation model, namely: Y = 9.93 + 0.272X1 + 0.121X2. F test results showed significant results, which means self-perception and knowledge about nutrition proved to have a significant effect on the decision to consume nutritious food. The conclusions in this study are 1) knowledge about nutrition has a significant influence on the decision to buy nutritious food, 2) self-perception of the influence of a significant effect on the decision to buy nutritious food and 3) knowledge about nutrition and self-perception has a significant influence simultaneously on the decision to buy nutritious food.